Colloidal organometallic synthesis of solution-processable barium titanate nanoparticles for nanoelectronic applications - Linke, Lara Kim; Dehm, Katharina; Gubanov, Kirill; Fink, Rainer; Szyja, Bartłomiej M.; Crisp, Ryan (Nanoscale, 2025)
Perovskite oxides like barium titanate (BaTiO3) exhibit desirable properties: notably high dielectric constants, piezoelectricity, and ferroelectricity, thereby enabling more advanced electronic devices and actuators. There are numerous synthesis procedures for BaTiO3, among which, nanoparticle syntheses are versatile and well-studied. However, colloidal organometallic synthesis is less commonly employed for this material despite offering processing advantages like facile compositional control and customizable surface chemistry. Here, an organometallic synthesis route is explored to produce colloidally stable BaTiO3 nanoparticles with oleyl alkoxide ligands. Subsequently, we further develop ligand exchange procedures with X-type ligands using KOH and oxalic acid to produce colloidal inks applicable for solution-processed nanocrystalline films for dielectrics in devices for which there is still a need for better nanoscale control. The BaTiO3 nanoparticles and films were characterized using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FT-IR), atomic force microscopy (AFM), Kelvin probe force microscopy (KPFM), and density functional theory (DFT), to understand their properties and to develop processes for device applications.
CRIS-Team Scopus Importer:2025-03-28